2014
DOI: 10.2460/ajvr.75.12.1029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peribulbar and retrobulbar regional anesthesia with bupivacaine in cats

Abstract: Objective-To compare effectiveness and complications associated with peribulbar and retrobulbar anesthesia with bupivacaine in cats. Animals-6 healthy adult cats. Procedures-Cats were sedated with dexmedetomidine and received a peribulbar injection of 0.5% bupivacaine (1.5 mL), iopamidol (0.5 mL), and saline (0.9% NaCl) solution (1 mL) or retrobulbar injection of 0.5% bupivacaine (0.75 mL) and iopamidol (0.25 mL) in a crossover study with ≥ 2 weeks between treatments. The contralateral eye was the control. Inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 55 publications
4
26
0
Order By: Relevance
“…Data from the present study support this as no change in corneal sensitivity was observed in those eyes, in which extraconal administration occurred. This was also reported in cats, where success rate of RBA was 50% (3 of 6) . The two successful RBA injections in the present study abolished corneal sensitivity for several hours following injection, which implies that when administered intraconally, 2 mL of bupivacaine is sufficient to produce corneal anesthesia in dogs up to (and maybe in excess of) 25 kg.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Data from the present study support this as no change in corneal sensitivity was observed in those eyes, in which extraconal administration occurred. This was also reported in cats, where success rate of RBA was 50% (3 of 6) . The two successful RBA injections in the present study abolished corneal sensitivity for several hours following injection, which implies that when administered intraconally, 2 mL of bupivacaine is sufficient to produce corneal anesthesia in dogs up to (and maybe in excess of) 25 kg.…”
Section: Discussionsupporting
confidence: 84%
“…The periocular skin sensation was tested using a “pin‐prick” technique with pressure applied to the periocular skin using the tip of a ballpoint pen at the mid‐dorsal eyelid, mid ventral eyelid, and lateral and medial canthi. The response was considered positive when the dog closed the eyelids or moved the head . Lastly, corneal sensitivity and then IOP were assessed as described earlier.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these aforementioned adverse effects were observed in the cats of the present study. The dose of bupivacaine used in this study was based on the veterinary literature, 34 results of experiments on IP administration of bupivacaine to humans, 15 and clinical experience with IP analgesia at the authors' institutions.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] In the present study, a final concentration of 0.25% was administered, and it is not known whether use of a higher concentration will increase the magnitude or duration of analgesia or cause adverse effects. The drug was diluted in saline solution to achieve a reasonable volume for anesthetic spread.…”
Section: Discussionmentioning
confidence: 99%